Comparison of control methods for H-bridge fed five-phase permanent magnet synchronous motors (peer reviewed!) - Jonsky, T.; Borcherding, Holger; Szymanski, P.; Wettlaufer, P.; Theßling, M. (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))
Three different control methods for a five-phase permanent magnet synchronous motor are presented and compared to each other. The control schemes include rotor-fixed approaches known as Field Orientated Control and stator-fix approaches like Direct Torque Control and Indirect Self Control. Simulations are carried out and are compared to measurement results.